Pengaruh Promosi Kesehatan Gigi Menggunakan Media Film Kartun dan Slide Terhadap Pengetahuan Siswa Sekolah Dasar - Taadi, Taadi; Suyatmi, Dwi (Journal of Oral Health Care, 2018)
Oral and dental health education is an effort to improve dental and oral health. Counseling must be attractive, attractive, without reducing its contents. Learning media is anything that can be used to stimulate thoughts, feelings of attention and ability. The purpose of this study was to determine the effect of dental health promotion using cartoon film and slide media on respondents' knowledge. This type of research uses a quasi-experimental design (quasi-experimental) The sampling technique was using quota sampling technique. The research treatment was by providing dental health promotion using cartoon film media and a 5 minute slide duration at different schools. The research subjects were given a questionnaire before intervention using cartoon films and slides and were given a questionnaire again as a posttest. Data analysis was performed using a different test to find out whether there was a difference between before and after treatment. The results of the study showed that the mean score difference between pretest and posttest on respondents after watching dental health promotion using slide media was 0.88, with a probability of 0.027. the first test and the second test with an average difference of -0.12. Dental health promotion using slides and cartoon films can increase the knowledge of elementary school students.